Study on Pressure Relief Effect and Rock Failure Characteristics with Different Borehole Diameters - Shiwei Liang; Long Zhang; Di Ge; Qiong Wang (Shock and Vibration)
Rock burst is a common tunnel and mine dynamic disaster, especially for deep buried tunnels, which often leads to tunnel construction delay and even induces tunnel collapse and subsidence of strata. Rock drilling is one of the effective pressure relief methods to prevent these disasters. In order to study the influence of borehole diameter on rock mass pressure relief effect, indoor acoustic emission characteristics and numerical simulation of rock samples with different borehole diameter were studied. The research result shows that with the increase in borehole diameter, the effect of borehole pressure relief is better. Different borehole diameters do not change the overall trend of acoustic emission evolution, but it will lead to different acoustic emission count characteristics of rock damage and failure, especially the maximum acoustic emission count characteristics and corresponding strain values. The existence of drilling will lead to the failure stress of rock in advance. Moreover, the existence of drilling causes a great change in the failure mode of the specimen.